Level of Anxiety of Final Semester Students in Completing Thesis for BK Students at PGRI University, West Sumatra - Marianto, Heru (Lembaga Riset Mutiara Akbar, 2023)
The background of this research is that there are students who feel nervous when dealing directly with the supervisor, there are students who are worried about meeting the supervisor and there are students who are afraid of the final assignment that has been made to be blamed or repeated. The purpose of this study is to describe: 1) The level of anxiety of students facing the thesis is seen from the physical aspect 2) The level of anxiety of students facing thesis is seen from the emotional aspect 3) The level of anxiety of students facing the thesis is seen from the mental and cognitive aspects. This research was conducted using a quantitative descriptive method. The sample of this study was 84 final semester counseling students at PGRI University, West Sumatra using a purvosive sampling technique. The instrument used is a questionnaire while for data analysis using percentage classification. The results of the study regarding the description of the level of anxiety of final semester students in completing their thesis on BK PGRI University West Sumatra students seen from the level of student anxiety in general are in the fairly high category, then in the physical aspect are in the low category, the emotional aspects are in the fairly high category and the mental and cognitive are in the high category. Based on the findings of this study it is recommended for students to be able to further improve their physical condition in working on their thesis and guidance with supervisors, thereby reducing student anxiety conditions caused by disturbances in the physical aspect in order to be able to complete thesis assignments without obstacles